Microstructures and mechanical properties of Mg-2%Zn-0.4%RE alloys - 乐启炽 张志强 邵志文 崔建忠 谢一 (Transactions of Nonferrous Metals Society of China, 2010)
The solidification microstructures and hardness of Mg-2%Zn （mass fraction） based alloys with addition of 0.4%Ce, 0.4%Gd, 0.4%Y or 0.4%Nd （mass fraction） were investigated, and the effects of the rare earth elements on the microstructures and mechanical properties of these alloys extruded at 310℃ were also compared. The results indicate that the trace rare earth Ce, Gd, Y or Nd in the Mg-2%Zn alloy has obviously different grain refinement effects on its solidification microstructures, and the as-cast and hot-extruded alloy with 0.4%Ce has the smallest average grain size and the highest strength. However, the extruded alloys containing 0.4%Nd or 0.4%Y with the elongation of 26.6% and 30%, respectively, show higher plasticity in spite of lower strength as compared with the alloy containing 0.4%Ce.